La part de la fiction. A propos de quelques documentaires argentins - Joaquín Manzi (Presses Universitaires du Mirail, 2009)
This paper describes the argentinian documentary production since the beginning of XXIth centuy, insisting on some hybrid films. The usual differences between fiction and documentary are questionned by three kinds of films. The first one is about a special kind of portraits, made on some men leaving in margins of the great city, those presented in F. León’s & M. Martínez’s Estrellas (2007), P. Trapero’s Naikor (2001), and U. Rossel’s Bonanza (2001). The second one is self personnal story assumed by two missing’s sons : A. Carri’s Los rubios (2003), and N. Prividera’s M (2007). The last one is about two artists on their diary work, Ricardo Longhini’s in Espejo para cuando me pruebe un smoking, by A. Fernández Mouján (2005), and Edgardo Cozarinsky’s, in Meykinof, by C. Guarini (2005).